Various illustrative brief glances at the flavour-cryptoexotic tetraquark states - Lucha Wolfgang (EPJ Web of Conferences)
Constituting the largest subset of multiquark states so far observed by experiment, tetraquark mesons carrying overall quark flavour quantum numbers identical to those of the (conventional) quark–antiquark mesons necessitate their particularly deliberate phenomenological analyses. A collection of (more or less recent) insights specific to the latter subclass of exotic hadrons bears the promise to enable even significant improvement in the understanding of these hadrons by theoretical approaches such as, among others, the framework of QCD sum rules.